Potential study and utilization of red fruit peels (Pandanus conoideus lam) as feed additive for native chicken production. Issue 1 (April 2020) - Saragih, D T R; Syamsu, J A; Purwanti, S; Pakiding, W
Abstract: Application of the use of red fruit ( Pandanus conoideus Lam) as a feed additive needs to be developed because it has antioxidant properties and as a preventive disease drug. The purpose of this review is to examine the use of red fruit peels as feed additives for native chickens. A literature study conducted by reviewing several journals with the results of the study showed that the use of red fruit peels in poultry is still limited to broilers. Red fruit has known properties as a cancer-preventing drug, hypertension, diabetes, and even HIV. Red fruit contains beta-carotene, tocopherol, oleic acid, and linoleic acid. It also contains unsaturated fatty acids, namely oleic acid, linoleic acid, linolenic acid, decanoic, omega 3, and omega 9. Parts used only in fruit juice, oil, and red fruit pulp, while the skin has not been utilized. Thus, the use of red fruit peels in free-range chickens as feed additives will provide new treasures in science and prospects for local, regional, national, and even international sluggish poultry fields.